Rheology of Semisolid Foods - Joyner, Helen S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Rheology of Semisolid Foods comprehensively covers the rheological behaviors and rheological testing of semisolid foods. Individual chapters focus on semisolid food structure, rheological and sensory behaviors, testing of various semisolid food behaviors, and factors that impact those behaviors. Special concentration is given to the relationships among semisolid food structures and mechanical properties and textures. The second section of this work presents a series of case studies on acid milk gels and yogurt which provide a practical illustration of the concepts presented in the preceding chapters, allowing readers to gain both conceptual knowledge of semisolid food rheology and an understanding of how that knowledge can be applied to a food system of choice. Individual components, processing parameters, and storage conditions can dramatically impact food functional properties and textures. Changing any of these factorscan cause significant microstructural alterations resulting in undesirable changes in product stability, functionality and texture. The lack of knowledge of how these factors impact the final food properties makes development of new food products a process of empirical trial rather than intentional design. A fundamental understanding food structure, function and texture relationships is critical for targeted design of food products. This text is a valuable reference for researchers looking to gain an understanding of how rheology works in semisolid food design and processing.
Part I: Semisolid Food Rheology -- Introduction: Measuring rheological properties of foods -- Semisolid foods: an overview -- Rheological testing for semisolid foods: Traditional rheometry -- Rheological testing for semisolid foods: Large amplitude oscillatory shear -- Rheological testing for semisolid foods: Tribology -- Rheology and semisolid food processing -- Structuring semisolid foods -- Rheological changes in semisolid foods during storage -- Sensory and oral processing of semisolid foods -- Relationships among semisolid food microstructures, rheological behaviors, and sensory attributes -- Part II: Case Studies -- Case study 1: impact of hydrocolloids on yogurt rheology, structure, and texture -- Case study 2: Yogurt tribology -- Case study 3: Impact of processing parameters on yogurt rheology -- Case study 4: Changes to yogurt rheological properties during storage. .
Keywords: Food science; Food Science